2019
DOI: 10.1039/c8nr10162k
|View full text |Cite
|
Sign up to set email alerts
|

High-speed scanning ion conductance microscopy for sub-second topography imaging of live cells

Abstract: High-speed scanning ion conductance microscopy (HS-SICM) reveals ultra-fast morphodynamics of live cells at a rate of 0.6 s per frame.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…The speed of approach curve measurement can be made much faster by employing instrumentation developed for fast scanning ion-conductance microscopy. 35 For instance, an ionic current of ~2.7 nA was measured with a precision of ±0.5 pA (i.e., ±0.02% of the ionic current) when an ~100 nm-diameter water-filled nanopipet traveled 2 μm in 4–40 ms, i.e., 50–500 μm/s. 36 In comparison with our setup, not only was the similar current measured more precisely despite much faster sampling, but also the approach velocity was ~100–1000 times faster.…”
Section: Resultsmentioning
confidence: 99%
“…The speed of approach curve measurement can be made much faster by employing instrumentation developed for fast scanning ion-conductance microscopy. 35 For instance, an ionic current of ~2.7 nA was measured with a precision of ±0.5 pA (i.e., ±0.02% of the ionic current) when an ~100 nm-diameter water-filled nanopipet traveled 2 μm in 4–40 ms, i.e., 50–500 μm/s. 36 In comparison with our setup, not only was the similar current measured more precisely despite much faster sampling, but also the approach velocity was ~100–1000 times faster.…”
Section: Resultsmentioning
confidence: 99%
“…This v z value attained here is more than 300 times improvement over the v z value used in a recent SICM imaging study on biological samples (50 nm/ms for r a = 50 nm) with a conventional design of SICM Z-scanner [34]. Very recently, the Schäffer group successfully increased v z up to 4.8 µm/ms for r a = 80-100 nm using their sample stage scanner and a step retraction sequence called 'turn step' [40]. Our v z value achieved for even 3-4 times smaller r a still surpasses their result.…”
Section: Evaluation Of Improved Vzmentioning
confidence: 98%
“…Since we have not yet introduced other devices proposed previously for increasing the temporal resolution, there are still room for further speed enhancement. One of candidates to be added is (i) the 'turn step' procedure (applying a step function to the Z-piezodriver) developed by Simeonov and Schäffer for rapid pipette retraction [40]. Other candidates would be (ii) further current noise reduction of the transimpedance amplifier in a high frequency region, and (iii) lock-in detection of AC current produced by modulation of the pipette Z-position with small amplitude [12].…”
Section: G Outlook For Higher Spatiotemporal Resolutionmentioning
confidence: 99%
“…Since piezo actuators used to move the probe have finite time response, the imaging rate depends on the image size and the number of pixels comprising the image. It has been demonstrated that it is possible to design and construct SICM that could be operated in high speed (HS) regime sufficient to follow highly dynamic processes in living cells (Ida et al, 2017;Simeonov & Schäffer, 2019a, 2019b.…”
Section: Sicm-fcmmentioning
confidence: 99%